Implantação de um sistema de gerenciamento de resíduos sólidos em uma fábrica de tintas - Rocha, Marçal Paim da (2006)
The industries and their productive processes are responsible for significant environmental pollution. Among those, there are the ink industries, whose products have considerable importance in the protection of surfaces for covering processes. This sector, as well as others, it uses resources and generates residues. The aim of the work is implant solid residues management system in an ink factory. The analysis of the process was carried through aiming at the characterization and quantification of the generated residues, as well as the orientation and training of the collaborators, actions for the segregation, reduction, reutilization, recycling and the definition of the final destination adequated of the residues. Besides the improvement of the environmental quality of the company, the administration of the solid residues permitted the acquisition of revenues with their commercialization for recycling, the development of a primer produced from the internal recycling of 90% of the residue of synthetic ink and their derived, attendance of a new consumer market, the improvement of the relationship between the company and its customers, as well as the awareness and the involvement of the collaborators with the environmental question. In the end of the work it was concluded that the company studied was able to reduce its environmental impacts and to become more competitive with regard to the market when considering the environmental variable in the taken decisions.